2011 IEEE 61st Electronic Components and Technology Conference (ECTC) 2011
DOI: 10.1109/ectc.2011.5898725
|View full text |Cite
|
Sign up to set email alerts
|

A new wafer-level packaging technology for MEMS with hermetic micro-environment

Abstract: We report a new wafer-level packaging technology for miniature MEMS in a hermetic micro-environment. The unique and new feature of this technology is that it only uses low cost wafer-level processes such as eutectic bonding, Bosch etching and mechanical lapping and thinning steps as compared to more expensive process steps that will be required in other alternative wafer-level technologies involving thru-silicon vias or membrane lids. We have demonstrated this technology by packaging silicon-based AlN microsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Figure 6b shows the measured phase noise (a measurement of the oscillator short term frequency stability) of the single chip oscillator and specifi cations, converted to 532 MHz, frequency reference for the global system for mobile communications (GSM), a common standard for mobile phones. The AlN/ CMOS oscillator demonstrates communications grade phase noise performance, and when combined with separately developed thermal stabilization 40 and wafer level packaging 41 techniques, it is a viable technology for integration with RF electronics in next-generation military radios and wireless handsets. The process fl ow used to fabricate the AlN microresonator over CMOS is shown in Figure 7 .…”
Section: Aln Resonators On Cmos Circuitsmentioning
confidence: 99%
“…Figure 6b shows the measured phase noise (a measurement of the oscillator short term frequency stability) of the single chip oscillator and specifi cations, converted to 532 MHz, frequency reference for the global system for mobile communications (GSM), a common standard for mobile phones. The AlN/ CMOS oscillator demonstrates communications grade phase noise performance, and when combined with separately developed thermal stabilization 40 and wafer level packaging 41 techniques, it is a viable technology for integration with RF electronics in next-generation military radios and wireless handsets. The process fl ow used to fabricate the AlN microresonator over CMOS is shown in Figure 7 .…”
Section: Aln Resonators On Cmos Circuitsmentioning
confidence: 99%
“…In the original reporting [2], a Ge-Au eutectic was used with the die wafer consisting of a metal stack of 20 nm of Ti / 100 nm of Pt / 500 nm of Au on AlN and the etched lid wafer consisting of a 20 nm of Ti / 100 nm of Pt / 440 nm of Au / 500 -700 nm of Ge / 100 nm of Au metal stack on the silicon lid substrate. Bonding was generally performed in the temperature range of 365-375 C for times ranging from 5 min to 15 min under 2-3 kN of pressure after an extended time, 20-30 minutes, at 320 C utilized for outgassing.…”
Section: Eutectic Bondingmentioning
confidence: 99%
“…Microchemical analysis on the bonded interface indicated that the intended Ge-Au eutectic contained a large amount of Si. It is likely, given the lower bonding temperatures and times utilized for the microresonator assembly described earlier [2], that the eutectic alloy was mostly Si-Au eutectic where the silicon was introduced from the substrate. Due to the required elevated temperatures, bonding times, and increased difficulty using Ge, an aSi-Au eutectic was chosen.…”
Section: Eutectic Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…Packaging in the MEMS industry has the role of protecting the structures against the surrounding environment, including external shocks, dust, humidity, air damping, and other damaging elements [4]- [7]. Unlike ordinary devices, most MEMS devices with moving parts cannot be directly molded with engineering plastic and require unique packaging structures.…”
Section: Introductionmentioning
confidence: 99%